2020
DOI: 10.3390/foods9030325
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Lipid-Based Delivery Systems as a Strategy to Increase Functionality of Bioactive Compounds

Abstract: Acquisition of a healthy lifestyle through diet has driven the food manufacturing industry to produce new food products with high nutritional quality. In this sense, consumption of bioactive compounds has been associated with a decreased risk of suffering chronic diseases. Nonetheless, due to their low solubility in aqueous matrices, high instability in food products during processing and preparation as well as poor bioavailability, the use of such compounds is sometimes limited. Recent advancements in encapsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 126 publications
0
12
0
Order By: Relevance
“…In recent years, several delivery nanocarrier-based formulations have been developed to modulate the release of bioactive compounds, including polyphenols such as catechins, quercetin, eugenol, epigallocatechin, curcumin, and tea polyphenols, demonstrating improvements in the solubility of these bioactive molecules, improving their bioavailability, absorption, and biological effects [155,156]. In this sense, in the past years, nanosuspensions, polymeric nanoparticles, nanocapsules, nanofibrous scaffolds, nanoemulsions, and nanoliposomes, among others, have been investigated to deliver polyphenols and improve its bioavailability and bioactivity [155,157]. However, concerns related to the nanoencapsulation of polyphenols have been reported, due to their varying structures, solubility, and fast oxidation under basic conditions [155].…”
Section: Food Matrix and Food Processingmentioning
confidence: 99%
“…In recent years, several delivery nanocarrier-based formulations have been developed to modulate the release of bioactive compounds, including polyphenols such as catechins, quercetin, eugenol, epigallocatechin, curcumin, and tea polyphenols, demonstrating improvements in the solubility of these bioactive molecules, improving their bioavailability, absorption, and biological effects [155,156]. In this sense, in the past years, nanosuspensions, polymeric nanoparticles, nanocapsules, nanofibrous scaffolds, nanoemulsions, and nanoliposomes, among others, have been investigated to deliver polyphenols and improve its bioavailability and bioactivity [155,157]. However, concerns related to the nanoencapsulation of polyphenols have been reported, due to their varying structures, solubility, and fast oxidation under basic conditions [155].…”
Section: Food Matrix and Food Processingmentioning
confidence: 99%
“…Reducing exposure to oxygen is one way to avoid the oxidation of fish oils. The encapsulation of lipophilic compounds in biocompatible materials with a nano-technique is a feasible means for achieving this purpose [ 10 , 11 ]. As a result, the encapsulation of CBLO can improve its stability, helping to avoid irradiation, oxidation, and thermal degradation while reducing the fishy smell.…”
Section: Introductionmentioning
confidence: 99%
“…As a solution, recent studies have revealed the use of nanostructured delivery systems such as nanoemulsions to encapsulate and protect β-carotene after oral consumption and enhance its delivery to intestinal barrier (Chen, Li, Li, McClements, & Xiao, 2017;Gasa-Falcon et al, 2020;Yi, Zhong, Zhang, Yokoyama, & Zhao, 2015). Β-carotene enriched nanoemulsions stabilised with pectin, lecithin, sodium caseinate, Tween 20 or sucrose palmitate, have been subjected to in vitro gastrointestinal digestion (GID) and the subsequent release of β-carotene has been determined (Gasa-Falcon et al, 2019;Salvia-Trujillo et al, 2013;Teixé-Roig et al, 2020).…”
Section: Introductionmentioning
confidence: 99%